2015
DOI: 10.1111/jfd.12419
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of Salmo salar (Linnaeus 1758) facing low abundance infestation of Caligus rogercresseyi (Boxshall & Bravo 2000), an object in the tank, and handling

Abstract: This study looks at how low infestation loads of adult Caligus rogercresseyi and other stressors affect the physiology of Salmo salar. Experimental fish groups were with (infested) or without (control) exposure to the parasite. The parasite cohort was followed for 78 days post-infestation (dpi), and only adult lice were observed. Additional stressors were applied at 60 and 75 dpi. The analysis included measurements of fish physiology and weight. Low-level infestations by adult C. rogercresseyi for more than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
(107 reference statements)
0
6
1
Order By: Relevance
“…The lactate values observed in this experiment were within the range of values reported for white seabream [55]. The absence of statistical differences in both treatments for lactate levels is not in agreement with the differences observed in other studies with fish parasites [57]. However, there was a tendency for a high level of lactate at 5 h after infestation.…”
Section: Discussioncontrasting
confidence: 68%
“…The lactate values observed in this experiment were within the range of values reported for white seabream [55]. The absence of statistical differences in both treatments for lactate levels is not in agreement with the differences observed in other studies with fish parasites [57]. However, there was a tendency for a high level of lactate at 5 h after infestation.…”
Section: Discussioncontrasting
confidence: 68%
“…With regards to growth, it was known that sea lice could reduce appetite, food-conversion efficiency and growth in fish 9 , 36 , 37 . Recently, it has been demonstrated that an infection with C. rogercresseyi is energetically demanding for Atlantic salmon, producing stress and disrupting fish physiology 15 , 38 – 40 . The results presented here confirm such effects, showing that SGR of moribund fish was significantly lower in coinfected fish, compared to fish infected only with P. salmonis .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that six adult C. rogercresseyi per fish will alter the fish's physiological response, affecting their primary and secondary responses (e.g., cortisol and glucose levels), as well as their tertiary response (fish weight). These results suggest that C. rogercresseyi infestation is energetically demanding, leading to an acute and chronic stress response and metabolic reorganization and thereby impacting fish welfare (González, Marín, & Vargas‐Chacoff, ).…”
Section: Introductionmentioning
confidence: 99%